Simulation and optimization studies on CsPbI3 based inorganic perovskite solar cells. (June 2021) - Jayan K, Deepthi; Sebastian, Varkey; Kurian, Joji
Highlights: DFT based absorption spectrum of the absorber layer is used for the modelling of the PSCs. Inorganic Cs based perovskite absorber layer was used for modelling. A high theoretical PCE of 15.6% was achieved for the optimized device configuration. The absorber layer parameters and back metal contacts influenced device performance. Abstract: Cesium lead iodide (CsPbI3 ) based perovskite solar cell (PSC) with inorganic electron and hole transport layers is simulated using SCAPS 1D to find optimum performance conditions for an all-inorganic PSC with maximum stability and efficiency. In this study, the absorption spectrum and bandgap of CsPbI3 absorber layer are computed with the help of density functional theory and the resulting spectrum is used as an input for device simulation. Further improvement of device performance is done by optimizing the work function of back electrode, absorber thickness, doping density as well as defect density. Under optimized conditions, a conversion efficiency of 11.99% is obtained with gold (Au) as back contact metal. The efficiency is enhanced to 15.6% for the FTO/ZnO/CsPbI3 /CuSbS2 /Se configuration, which uses Se instead of Au as back contact metal, indicating the possibility of replacing the expensive Au with Se as back contact metal in PSCs. The photovoltaic performance parameters achieve their maximum value at an absorber thickness of 547 nm and defect and dopant density of 2.07 × 10 14 cm −3 and 1 × 10 15 cm −3 respectively. The study shows that the PCE of inorganic CsPbI3 based PSCs can be improved significantly by introducing a low cost back contact metal Se and using inorganic transport materials, ZnO and CuSbS2 .